2021
DOI: 10.1007/s00784-021-03867-y
|View full text |Cite
|
Sign up to set email alerts
|

High-level laser therapy versus scalpel surgery in the treatment of oral lichen planus: a randomized control trial

Abstract: Objective To compare the clinical effectiveness of various types of high-level laser therapy (HLLT) toward scalpel excision for the surgical treatment of erosive oral lichen planus (OLP). Materials and methods The total number of 128 individuals were enrolled in the study. The 35 did not meet the inclusion criteria due to malignancy signs and presence of diabetes mellitus. In total, 8 were lost to follow-up, and 10 were excluded from the analysis, due to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…All results were summarized and are synthesized in Table 3 and Table 4 . The chosen articles were Gambino et al (2018) [ 28 ], Mirza et al 143 (2018) [ 29 ], Mutafchieva et al (2018) [ 30 ], Lavaee et al (2019) [ 31 ], Khater et al (2020) [ 32 ], Nammour et al (2021) [ 26 ] and Tarasenko et al (2021) [ 33 ] as they met all the inclusion criteria proposed in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All results were summarized and are synthesized in Table 3 and Table 4 . The chosen articles were Gambino et al (2018) [ 28 ], Mirza et al 143 (2018) [ 29 ], Mutafchieva et al (2018) [ 30 ], Lavaee et al (2019) [ 31 ], Khater et al (2020) [ 32 ], Nammour et al (2021) [ 26 ] and Tarasenko et al (2021) [ 33 ] as they met all the inclusion criteria proposed in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the type of source used in PBM, as well as the parameters established in each study, we observed that in four cases the diode laser was used (Gambino et al [ 28 ], Mirza et al [ 29 ], Mutafchieva et al [ 30 ] and Lavaee et al [ 31 ]), while Khater et al [ 32 ] and Tarasenko et al [ 33 ] used the Nd–YAG laser at the same wavelength of 1064 nm, and Nammour et al [ 26 ] used the He–Ne laser. The power used ranged between 25 mW in Lavaee et al [ 31 ] and 3 W in Tarasenko et al [ 33 ], while the minimum wavelength used was 630 nm, and the maximum one was 1064 nm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations